IMPROVEMENT OF ELECTROCHEMICAL PROCESSES IN HYDROGEN POWER ENGINEERING - Covaliova O.V.; Covaliov V.V.; Duca Gh.G.; Ivanov M.V. (Problems of the Regional Energetics)
The possibility is studied of using the three-dimensional voluminous-porous electrodes made of the carbonic-fibrous materials and foamy metals, which surface is covered with Ni-Re alloy, for hydrogen electrochemical generation. Electrode surface modification makes it possible to obtain high reactive surface with low overvoltage of hydrogen evolution. The design is given of the developed compact electrochemical reactors for hydrogen power engineering. The method is described of oxygen-hydrogen mixture separation in the water electrolysis processes.